The conundrum of low achievement and feedback for learning. Issue 2 (17th February 2020) - Pitt, Edd; Bearman, Margaret; Esterhazy, Rachelle
Abstract: The literature on improving student engagement with assessment and feedback has a tendency to treat all students as if they are the same. Students with lower levels of attainment are generally under-represented within empirical studies and their feedback behaviours are less well understood. The recent drive to improve student assessment and feedback literacy and the move from 'feedback' being information about a task to being a process of understanding and using performance information is a larger conceptual leap for some students than others. In this paper, we consider issues surrounding the transition to new modes of feedback, focussing on what is needed for those who find study difficult and persistently are disappointed by their levels of attainment, to benefit from and take advantage of our feedback pedagogies. We examine literature advocating strategies such as increasing agency, using praise, developing feedback literacy and cultivating a growth mind-set. We argue that students who underachieve may benefit from strong relationships with educators and peers, exposure to feedback rich, low stakes environments, which permit repeated integrations of practice and feedback, and building feedback literacy through peer assessment activities.